SYNTHESIS, CHARACERIZATION AND ANTIOXIDANT ACTIVITY OF CURCUMINOID COMPLEXES - Sivalingam Lakshmanan (International Journal of Modern Agriculture, 2020)
Since an ancient day, people have used plants and their extracts to cure various diseases. Plants and their extracts are containing several bio-active compounds, which possess different biological activities. Curcumin/their derivatives have a much biological activity such as anti-oxidant, anti-inflammatory, anti-cancer, anti-bacterial, etc. Poor bioavailability is one of the drawback curcumin. To enhance it’s this issue we synthesized curcuminoid copper complexes. The synthesized ligand and complexes are well characterized by spectroscopic techniques. The complex and ligand synthesized to study its antioxidant activity of the curcumin. The three-dimensional structure was optimized using the Gaussian software.